Cryptococcus Neoformans Modulates Extracellular Killing by Neutrophils - Qureshi, Asfia; Grey, Angus; Rose, Kristie; Schey, Kevin; Del Poeta, Maurizio (Frontiers in Microbiology, 2011)
We recently established a key role for host sphingomyelin synthase (SMS) in the regulation of the killing activity of neutrophils against Cryptococcus neoformans. In this work, we studied the effect of C. neoformans on the killing activity of neutrophils and whether SMS would still be a player against C. neoformans in immunocompromised mice lacking T and NK cells (Tgε26 mice). To this end, we analyzed whether C. neoformans would have any effect on neutrophil survival and killing in vitro and in vivo. We show that unlike C. albicans, neither the presence nor the capsule size of C. neoformans cells have any effect on neutrophil viability. Interestingly, melanized C. neoformans cells totally abrogated the killing activity of neutrophils. Next, we monitored how exposure of neutrophils to C. neoformans cells would interfere with any further killing activity of the medium and found that pre-incubation with live but not “heat-killed” fungal cells significantly inhibits further killing activity of the medium. We next studied whether activation of SMS at the site of C. neoformans infection is dependent on T and NK cells. Using matrix-assisted laser desorption-ionization (MALDI) tissue imaging in infected lung we found that similarly to previous observations in the isogenic wild type CBA/J mice, SM 16:0 levels are significantly elevated at the site of infection in mice lacking T and NK cells but only at early time points. This study highlights that C. neoformans may negatively regulate the killing activity of neutrophils and that SMS activation in neutrophils appears to be partially independent of T and/or NK cells.